Preparation method of sintered neodymium-iron-boron permanent magnet, sintered neodymium-iron-boron permanent magnet and application

CN122991844APending Publication Date: 2026-10-27ANHUI FUXIN MAGNETIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416445.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0034]本申请提供的烧结钕铁硼永磁体,基础合金中复合添加对应含量的 Cu、Ga, Co及余量的Fe,通过控制轻稀土(Nd,Pr)含量,在Cu的作用下,促进形成低熔点、高均匀性的富Nd晶界相,优化了Tb沿晶界的扩散通道,确保在630-670℃低温下Tb仍有足够的扩散速率;在Ga的作用下,显著提高晶界相对主相晶粒的润湿性,使Tb扩散后在主相表层形成的“壳层”厚度更加均匀,避免局部富集或缺失; Co部分取代Fe,直接提高主相Nd2Fe14B的居里温度(Tc),从本征层面降低了矫顽力和剩磁的温度系数(α、β),三者协同作用并与晶界扩散工艺的协同设计,系统性地优化磁体的矫顽力温度系数、剩磁温度系数和高温不可逆损失,同时保持高室温磁性能,从而提高磁体的高温磁性能稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991844A_ABST
    Figure CN122991844A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of rare earth permanent magnet materials, in particular to a preparation method of sintered neodymium-iron-boron permanent magnets, the sintered neodymium-iron-boron permanent magnets and applications. The sintered neodymium-iron-boron permanent magnets provided by the application comprise a base alloy, and corresponding contents of Cu, Ga, Co and the balance of Fe are added in the base alloy. By controlling the content of light rare earth (Nd, Pr), the synergistic design of the base alloy composition and the grain boundary diffusion process, the temperature coefficient of coercivity, the temperature coefficient of remanence and the high-temperature irreversible loss of the magnet are systematically optimized, and meanwhile, the high-temperature magnetic performance stability of the magnet is improved while the high-temperature magnetic performance is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rare earth permanent magnet materials technology, and more specifically, to a method for preparing sintered NdFeB permanent magnets, the sintered NdFeB permanent magnets, and their applications. Background Technology

[0002] Sintered neodymium iron boron (Nd-Fe-B) permanent magnet materials possess extremely high remanence and energy product, making them indispensable key materials in modern high-tech products. With the rapid development of high-end equipment such as drive motors for new energy vehicles, wind turbines, and energy-saving industrial motors, increasingly stringent requirements are being placed on the high-temperature performance and coercivity of Nd-Fe-B magnets. These applications require magnets to operate stably for extended periods at temperatures ranging from 120 to 180°C or even higher. The performance degradation of magnets at high temperatures mainly includes two aspects: first, reversible degradation, where magnetic properties decrease with increasing temperature but recover upon cooling, determined by the intrinsic properties of the material and commonly described by the temperature coefficient of remanence (α) and the temperature coefficient of coercivity (β); and second, irreversible degradation, which is the permanent performance loss that occurs under high temperatures and demagnetizing fields, directly threatening the long-term operational reliability of equipment.

[0003] However, commercially available sintered NdFeB magnets without heavy rare earth elements have low coercivity (<1200 kA / m), and the main Nd2Fe phase... 14 Neodymium iron boron (NdFeB) magnets have a low Curie temperature (Tc = 312℃), making it difficult to meet the requirements for use under the aforementioned high-temperature conditions. Therefore, improving the high-temperature magnetic performance stability of NdFeB magnets, especially systematically optimizing the coercivity temperature coefficient, remanence temperature coefficient, and high-temperature irreversible losses, has become a key technical problem that the industry urgently needs to solve.

[0004] Currently, there are two main technical approaches to improving the high-temperature stability of sintered NdFeB magnets:

[0005] Firstly, the traditional heavy rare earth alloying method. This involves adding heavy rare earth elements Dy and Tb during the smelting process to replace Nd in the 2:14:1 main phase, forming (HRE,Nd)2Fe with a higher anisotropic field. 14 The B phase is used to improve the coercivity and thermal stability of the magnet. While this method effectively enhances coercivity, it has significant drawbacks: First, heavy rare earth resources are scarce and expensive, accounting for 30%–50% of the price of NdFeB finished products. Second, due to the antiferromagnetic coupling between heavy rare earth atoms and Fe atoms, adding large amounts of heavy rare earth inevitably leads to a significant decrease in remanence and energy product of the magnet. Furthermore, the overall alloying method has low heavy rare earth utilization; a large amount of heavy rare earth enters the interior of the main phase grains rather than concentrating on the surface regions of the grains most in need of strengthening, resulting in low efficiency in improving coercivity with the same amount of heavy rare earth.

[0006] Secondly, grain boundary diffusion technology. Based on the coercivity mechanism of sintered NdFeB permanent magnets, demagnetizing domains first form on the grain surface, making the grain surface the weakest link in the magnet. Based on this principle, grain boundary diffusion technology was proposed in 2005. The specific method involves preparing a coating of heavy rare earth metals, alloys, or compounds on the surface of the sintered NdFeB magnet. Through high-temperature diffusion treatment at approximately 900℃, the heavy rare earth elements enter the magnet's interior along the grain boundaries and preferentially distribute at the edges of the main phase grains, forming a shell structure with a high anisotropic field. This suppresses the nucleation of demagnetizing domains and improves the coercivity of the permanent magnet. The advantages of grain boundary diffusion technology are: only a small amount of heavy rare earth is needed to significantly improve coercivity, while having minimal impact on remanence; the utilization rate of heavy rare earth is significantly higher than that of traditional alloying methods. Currently, grain boundary diffusion technology has been rapidly industrialized and has become one of the mainstream technologies for producing high-coercivity magnets in the industry.

[0007] However, existing grain boundary diffusion technologies still have the following shortcomings:

[0008] First, the optimization of high-temperature stability is not systematic. Although traditional heavy rare earth grain boundary diffusion technology can significantly improve the coercivity of magnets, it cannot effectively optimize the remanence temperature coefficient. At present, most research and production practices only focus on the magnitude of the coercivity improvement, while lacking systematic and coordinated optimization of high-temperature stability indicators such as the coercivity temperature coefficient (β), the remanence temperature coefficient (α), and high-temperature irreversible loss (H_irr).

[0009] Second, there are limitations to conventional high-temperature diffusion processes. Existing grain boundary diffusion processes typically operate at diffusion temperatures between 800 and 950°C. While this temperature range facilitates rapid diffusion of heavy rare earth elements (HREEs) along grain boundaries, it also exacerbates bulk diffusion of HREEs into the main phase grains. This results in some HREEs entering the grain interior rather than concentrating on the surface shell, leading to increased remanence loss. Furthermore, the improvement in the overall temperature stability of the magnet from high-temperature diffusion treatment is limited.

[0010] Third, there is a lack of synergistic design between the basic alloy composition and the diffusion process. Existing technologies often treat the composition design of the basic alloy and the grain boundary diffusion process as independent technical steps, failing to fully consider the influence of specific added elements (such as Cu, Ga, Co, etc.) in the basic alloy on diffusion channels, grain boundary wettability, and the intrinsic temperature characteristics of the main phase. Studies have shown that elements such as Cu and Ga can form non-ferromagnetic NdCu and Nd6Fe at grain boundaries. 13 Ga grain boundary phases are beneficial for enhancing the magnetic isolation effect of grain boundaries on the main phase grains; partial substitution of Fe by Co can increase the Curie temperature of the main phase and reduce the temperature coefficient. However, current technology has not yet organically combined the composite addition of Cu, Ga, and Co in the base alloy with grain boundary diffusion processes to systematically optimize the high-temperature magnetic stability of the magnet.

[0011] In summary, how to systematically optimize the coercivity temperature coefficient, remanence temperature coefficient, and high-temperature irreversible loss of magnets through the synergistic design of basic alloy composition and grain boundary diffusion process with extremely low heavy rare earth content, while maintaining high room temperature magnetic properties, in order to improve the high-temperature magnetic stability of magnets, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0012] In view of this, the present invention addresses the deficiencies of the existing technology by providing a method for preparing sintered NdFeB permanent magnets with optimized high-temperature magnetic performance stability, as well as the sintered NdFeB permanent magnets and their applications.

[0013] To solve the above problems, this application adopts the following technical solution:

[0014] One of the objectives of this application is to provide a method for preparing sintered NdFeB permanent magnets, comprising the following steps:

[0015] (1) Prepare a base alloy, wherein the composition of the base alloy is (Nd, Pr) by weight percentage. a Fe bal B b M, where a ranges from 31 to 33 wt%, b ranges from 0.98 to 1.05 wt%, and M is a composite additive element containing 0.10 to 0.30 wt% Cu, 0.05 to 0.15 wt% Ga, and 0.10 to 0.30 wt% Co, with the balance being Fe;

[0016] (2) The base alloy is prepared into powder, oriented by magnetic field and pressed into shape, and then vacuum sintered at 1060-1080℃, followed by first-stage aging treatment to obtain sintered magnet blank;

[0017] (3) A Tb-Al based alloy thin film is deposited on the surface of the sintered magnet blank as a diffusion source, and then grain boundary diffusion heat treatment is carried out at 630-670°C under inert atmosphere protection.

[0018] (4) Perform post-processing on the magnet after diffusion treatment.

[0019] In some embodiments, in step (1), the value of a ranges from 31.5 to 32.5 wt%, the content of Cu is 0.15 to 0.25 wt%, the content of Ga is 0.08 to 0.12 wt%, and the content of Co is 0.15 to 0.25 wt%.

[0020] In some embodiments, in step (2), the average particle size of the powder is 3.0 to 4.0 μm; the holding time of the vacuum sintering is 2 to 4 hours; the temperature of the first-stage aging treatment is 900 to 920°C, and the holding time is 1 to 2 hours; the density of the sintered magnet blank is ≥7.5 g / cm³.

[0021] In some embodiments, in step (3), the Tb-Al based alloy is Tb 70 Al 30 The thickness of the Tb-Al based alloy film is 10–30 μm.

[0022] In some embodiments, in step (3), the deposition method of the Tb-Al based alloy thin film is magnetron sputtering, vacuum evaporation, or ion plating; the conditions for magnetron sputtering are: a vacuum degree better than 5.0 × 10⁻⁶. -4 The pressure is 0.5–1.0 Pa, and the sputtering power is 100–200 W; the grain boundary diffusion heat treatment time is 8–12 hours.

[0023] In some embodiments, step (4) of post-processing the diffused magnet includes: machining and surface protection treatment of the diffused magnet.

[0024] The second objective of this application is to provide a sintered NdFeB permanent magnet, which is prepared by any of the methods described in this application, wherein the amount of heavy rare earth Tb in the permanent magnet is ≤0.8 wt.

[0025] In some embodiments, the permanent magnet meets the following performance indicators:

[0026] Remanence at room temperature Br ≥ 1.42 T;

[0027] Room temperature coercivity Hcj ≥ 1800 kA / m;

[0028] Temperature coefficient of coercivity β (20-150℃) ≥ -0.55 % / ℃;

[0029] The temperature coefficient of remanence α (20-150℃) ≥ -0.115 % / ℃;

[0030] Irreversible loss at 150℃ H_irr(150℃) ≤ 3.5%.

[0031] In some embodiments, the permanent magnet satisfies: coercivity temperature coefficient β (20-150℃) ≥ -0.53% / ℃, and / or remanence temperature coefficient α (20-150℃) ≥ -0.113% / ℃, and / or irreversible loss at 150℃ H_irr (150℃) ≤ 3.1%.

[0032] The third objective of this application is to provide the application of any of the methods described in this application or any of the permanent magnets described in this application in new energy vehicle drive motors, wind turbines, or high-temperature industrial motors.

[0033] The present application adopts the above technical solution, and its beneficial effects are as follows:

[0034] The sintered NdFeB permanent magnet provided in this application incorporates Cu, Ga, Co, and the balance Fe in the base alloy. By controlling the content of light rare earth elements (Nd, Pr), Cu promotes the formation of a low-melting-point, highly uniform Nd-rich grain boundary phase, optimizing the diffusion channels of Tb along the grain boundaries and ensuring sufficient diffusion rate of Tb at low temperatures of 630-670℃. Ga significantly improves the wettability of the grain boundaries relative to the main phase grains, resulting in a more uniform "shell" thickness formed on the surface of the main phase after Tb diffusion, avoiding local enrichment or absence. Co partially replaces Fe, directly increasing the Nd2Fe content of the main phase. 14 The Curie temperature (Tc) of B intrinsically reduces the temperature coefficients (α, β) of coercivity and remanence. The synergistic effect of these three factors, along with the synergistic design of the grain boundary diffusion process, systematically optimizes the temperature coefficients of coercivity, remanence, and high-temperature irreversible losses of the magnet, while maintaining high room temperature magnetic properties, thereby improving the high-temperature magnetic property stability of the magnet. Attached Figure Description

[0035] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0036] Figure 1 A flowchart illustrating the steps of a method for preparing a sintered NdFeB permanent magnet according to an embodiment of the present invention.

[0037] Figure 2 This is a schematic diagram comparing the high-temperature stability of the embodiments and comparative examples provided by the present invention. Detailed Implementation

[0038] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0039] In the description of this application, it should be understood that the terms "upper", "lower", "horizontal", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0040] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0041] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments.

[0042] Please see Figure 1 The following is a flowchart of the preparation method of sintered NdFeB permanent magnets provided for one of the purposes of this application, which includes the following steps (1) to (4). The specific implementation of each step is described in detail below.

[0043] Step (1) Preparation of the base alloy: The composition of the base alloy, by weight percentage, is: (Nd, Pr) a Fe bal B b M, where a ranges from 31 to 33 wt%, b ranges from 0.98 to 1.05 wt%, and M is a composite additive element containing 0.10 to 0.30 wt% Cu, 0.05 to 0.15 wt% Ga, and 0.10 to 0.30 wt% Co, with the balance being Fe.

[0044] Further, in step (1), the value of a ranges from 31.5 to 32.5 wt%, the content of Cu is 0.15 to 0.25 wt%, the content of Ga is 0.08 to 0.12 wt%, and the content of Co is 0.15 to 0.25 wt%.

[0045] It is understandable that the basic alloy composition can be adjusted. The total amount of (Nd, Pr) can be adjusted within the range of 31-33 wt%, and the Pr / Nd ratio can be flexibly adjusted according to the cost and supply of raw materials. The Cu content can vary within the range of 0.10-0.30%, the Ga content can vary within the range of 0.05-0.15%, and the Co content can vary within the range of 0.10-0.30%, preferably Cu is 0.15-0.25%, Ga is 0.08-0.12%, and Co is 0.15-0.25%. A trace amount (≤0.10 wt%) of Nb or Zr can be added to refine the grains, but the presence of Cu, Ga, and Co must be ensured.

[0046] It is understood that this embodiment limits the basic alloy to contain a composite addition of 0.10-0.30% Cu, 0.05-0.15% Ga, and 0.10-0.30% Co (with Fe as the balance), with the light rare earth (Nd, Pr) content controlled at 31-33%. Cu promotes the formation of a low-melting-point, highly homogeneous Nd-rich grain boundary phase, optimizing the Tb diffusion channels along the grain boundaries and ensuring sufficient Tb diffusion rate at low temperatures of 630-670℃. Ga significantly improves the wettability of the grain boundaries relative to the main phase grains, resulting in a more uniform shell thickness formed on the main phase surface after Tb diffusion, avoiding local enrichment or deficiency. Co partially replaces Fe, directly increasing the Nd2Fe content of the main phase. 14 The Curie temperature (Tc) of boron intrinsically reduces the temperature coefficients (α, β) of coercivity and remanence. The combined addition of Cu, Ga, and Co creates a grain boundary structure (broadened, continuous, and with good wettability) that is most favorable for Tb diffusion, allowing high coercivity to be achieved with only extremely low amounts of heavy rare earth elements (≤0.8 wt%).

[0047] Step (2): The base alloy is prepared into powder, oriented by magnetic field and pressed into shape, and then vacuum sintered at 1060-1080℃. Then, it is subjected to first-stage aging treatment to obtain sintered magnet blank.

[0048] In this embodiment, the average particle size of the powder is 3.0–4.0 μm; the holding time for vacuum sintering is 2–4 hours; the temperature for the first-stage aging treatment is 900–920°C, and the holding time is 1–2 hours; the density of the sintered magnet blank is ≥7.5 g / cm³.

[0049] It is understandable that by preparing the base alloy into powder and controlling the particle size, sintering activity is ensured while avoiding oxidation caused by excessively fine powder, thus providing a prerequisite for high orientation (high Br). Vacuum sintering followed by a first-stage aging treatment yields a fully dense, high-density sintered body, while simultaneously promoting grain boundary phase homogenization, allowing Cu and Ga to pre-distribute at the grain boundaries, forming pre-fabricated diffusion channels.

[0050] Step (3): Deposit a Tb-Al based alloy thin film on the surface of the sintered magnet blank as a diffusion source, and then perform grain boundary diffusion heat treatment at 630-670℃ under inert atmosphere protection.

[0051] In this embodiment, in step (3), the Tb-Al based alloy is Tb 70 Al 30 The thickness of the Tb-Al based alloy film is 10–30 μm.

[0052] In this embodiment, in step (3), the deposition method of the Tb-Al based alloy thin film is magnetron sputtering, vacuum evaporation, or ion plating; the conditions for magnetron sputtering are: vacuum degree better than 5.0 × 10⁻⁶. -4 Pa, argon gas is introduced to 0.5-1.0 Pa, sputtering power is 100-200 W.

[0053] It is understood that this embodiment uses a Tb-Al based alloy (preferably Tb). 70 Al 30 (Atomic ratio), 10-30 μm thin films are deposited by magnetron sputtering (vacuum evaporation or ion plating as alternatives). Tb forms (Nd,Tb)₂Fe. 14 The anisotropic field of the B-shell is much higher than that of Dy, which is the material basis for "efficiently improving coercivity with extremely low dosage". Al and Tb form a eutectic alloy, which significantly reduces the melting point of the diffusion source. This allows the Tb-Al alloy to melt and spread along the grain boundaries at a low temperature of 630-670℃, solving the problem that pure Tb has too high a melting point (1356℃) to diffuse at low temperatures. Precise control of the film thickness of 10-30 μm ensures sufficient diffusion source while avoiding excessive waste, achieving precise control of heavy rare earth dosage ≤0.8 wt%. Uniform deposition ensures consistent performance of the entire batch of magnets.

[0054] It is understandable that the diffusion source, excluding Tb 70 Al 30 Alternatively, Tb-Al-Cu or Tb-Al-Ga ternary alloys can be used; or Dy can be used to partially replace Tb (e.g., Tb...). 0.5 Dy 0.5 ) 70 Al 30 In addition to magnetron sputtering, deposition methods can include vacuum evaporation or ion plating, and the film thickness can be adjusted within the range of 10-30 μm.

[0055] Furthermore, the grain boundary diffusion heat treatment time is 8 to 12 hours.

[0056] It is understood that in this embodiment, grain boundary diffusion is carried out under an inert atmosphere at 630-670℃ for 8-12 hours. Below 630℃, the Tb-Al alloy has a high viscosity after melting, resulting in insufficient driving force for diffusion along grain boundaries and a failure to achieve the required increase in coercivity (Hcj≥1800 kA / m). Above 670℃, bulk diffusion intensifies, and heavy rare earth elements enter the grain interior, not only wasting heavy rare earth elements but also causing a significant decrease in Br due to antiferromagnetic coupling. This embodiment selects 630-670℃, which falls precisely within the "grain boundary liquid phase spreading" window region. Tb mainly penetrates along grain boundaries (rather than through the lattice), significantly suppressing bulk diffusion into the grain interior, protecting the magnetic moment of the grain core, and minimizing remanence loss (Br remains ≥1.42T).

[0057] Furthermore, 8-12 hours ensures sufficient diffusion depth of Tb along the grain boundaries (entering the interior of the magnet), while the Cu, Ga, and Co in the base alloy fully react with the infiltrated Tb and the original Nd-rich phase to form a thermodynamically stable grain boundary phase structure. This stable structure is not easily softened or reconstructed at a high temperature of 150℃, directly reducing irreversible losses at high temperatures (H_irr(150℃)≤ 3.5%).

[0058] It should be noted that the heat treatment process is adjustable; the diffusion temperature can be selected within the range of 630-670℃, and the holding time can be adjusted within 8-12 hours. Generally speaking, higher temperatures or longer times are suitable for larger magnets, while lower temperatures or shorter times are suitable for smaller magnets. Specific optimization can be achieved by testing the performance under different process conditions.

[0059] Step (4) Perform post-processing on the magnet after diffusion treatment.

[0060] In this embodiment, step (4) of post-processing the diffused magnet includes: machining and surface protection treatment of the diffused magnet.

[0061] The sintered NdFeB permanent magnet provided in this application incorporates corresponding amounts of Cu, Ga, Co, and the balance Fe into the base alloy. By controlling the content of light rare earth elements (Nd, Pr) and through the synergistic design of the base alloy composition and grain boundary diffusion process, the coercivity temperature coefficient, remanence temperature coefficient, and high-temperature irreversible loss of the magnet are systematically optimized, while maintaining high room temperature magnetic properties, thereby improving the high-temperature magnetic stability of the magnet.

[0062] This application also provides a sintered NdFeB permanent magnet, which is prepared by the method described in any of the above methods, wherein the amount of heavy rare earth Tb in the permanent magnet is ≤0.8 wt.

[0063] In some embodiments, the permanent magnet meets the following performance indicators:

[0064] Remanence at room temperature Br ≥ 1.42 T;

[0065] Room temperature coercivity Hcj ≥ 1800 kA / m;

[0066] Temperature coefficient of coercivity β (20-150℃) ≥ -0.55 % / ℃;

[0067] The temperature coefficient of remanence α (20-150℃) ≥ -0.115 % / ℃;

[0068] Irreversible loss at 150℃ H_irr(150℃) ≤ 3.5%.

[0069] In some embodiments, the permanent magnet satisfies: coercivity temperature coefficient β (20-150℃) ≥ -0.53% / ℃, and / or remanence temperature coefficient α (20-150℃) ≥ -0.113% / ℃, and / or irreversible loss at 150℃ H_irr (150℃) ≤ 3.1%.

[0070] It is understood that the sintered NdFeB permanent magnets provided in this embodiment, under the same heavy rare earth content, have improved coercivity temperature coefficient β from approximately -0.55% / ℃ to over -0.53% / ℃, remanence temperature coefficient α from approximately -0.115% / ℃ to over -0.113% / ℃, and irreversible loss at 150℃ from 4.5% to below 3.1%. Room temperature remanence is well maintained (≥1.42 T), and coercivity (≥1800 kA / m) is comparable to or higher. Heavy rare earth utilization is higher, resulting in significant cost advantages.

[0071] This application also provides the application of any of the methods described in this application or any of the permanent magnets described in this application in new energy vehicle drive motors, wind turbines or high-temperature industrial motors.

[0072] The sintered NdFeB permanent magnet provided in this embodiment combines high torque (high Br), strong anti-demagnetization ability (high Hcj), and high temperature and long life (superior α, β, H_irr) at extremely low heavy rare earth costs, making it a perfect match for the operating conditions of new energy vehicle drive motors (oil-cooled / water-cooled high temperature environment) and wind turbines (long-term maintenance-free), and has significant commercial promotion value.

[0073] The magnet prepared by this invention is particularly suitable for applications requiring high-temperature stability of magnets, such as drive motors for new energy vehicles, wind turbines, and high-temperature industrial motors. It can also be applied to other permanent magnet devices that require high coercivity and good temperature stability.

[0074] The technical solutions described above in this application will be explained in detail below with reference to specific embodiments.

[0075] I. Example 1 (E1)

[0076] This embodiment 1 provides a method for sintering NdFeB permanent magnets, the specific steps of which are as follows:

[0077] 1. Preparation of basic alloys

[0078] The base alloy is formulated by weight percentage as follows: 32.0 wt% (Nd, Pr) (where the weight ratio of Nd to Pr is 4:1), 1.0 wt% B, and the composite additive element M consists of 0.20 wt% Cu, 0.10 wt% Ga and 0.20 wt% Co, with the balance being Fe and unavoidable impurities.

[0079] The raw materials in the above proportions were vacuum induction melted and cast into alloy ingots under argon protection. The ingots were then crushed into fine powder with an average particle size of 3.5 μm using a combination of hydrogen pyrolysis (HD) and air jet milling. This particle size range ensures good sintering activity and orientation.

[0080] 2. Powdering and Sintering

[0081] The powder was oriented and shaped in a magnetic field of 1.8 T, and then cold isostatically pressed to obtain a green blank. The green blank was vacuum sintered at 1070℃ for 3 hours, cooled, and then subjected to a first-stage aging treatment at 900℃ for 1.5 hours to obtain a high-density sintered magnet blank (density ≥ 7.5 g / cm³). The initial magnetic properties of the obtained blank at room temperature were measured to be: Br≈1.42 T, Hcj≈1350kA / m.

[0082] 3. Low-temperature grain boundary diffusion treatment

[0083] First, the diffusion source target is prepared. According to Tb... 70 Al 30 Pure Tb and pure Al were weighed out according to the atomic percentage ratio, placed in a vacuum induction melting furnace, melted at 1600℃ under argon protection, cast into ingots, and then processed into magnetron sputtering targets by forging and wire cutting.

[0084] The sintered magnet blank was machined into samples with dimensions of 40mm × 40mm × 10mm. After grinding, cleaning, and drying, it was placed in the vacuum chamber of a magnetron sputtering equipment. The vacuum was evacuated to a level better than 5.0 × 10⁻⁶. -4 Pa, high-purity argon gas was introduced to 0.8 Pa, and deposition was performed with a sputtering power of 150 W. The deposition time was controlled to achieve Tb 70 Al 30 The thickness of the alloy film is 20 μm.

[0085] Subsequently, under an argon atmosphere, the sample with the deposited film was placed in a heat treatment furnace and heated to 650°C at a rate of 5°C / min, and held at that temperature for 10 hours for grain boundary diffusion heat treatment. After the holding period, the sample was cooled to below 150°C in the furnace and then removed.

[0086] 4. Post-processing

[0087] After diffusion treatment, the magnet is machined (grinding, slicing, chamfering), and after degreasing, pickling and activation, a Ni-Cu-Ni three-layer composite protective layer is electroplated to finally obtain the finished magnet.

[0088] 5. Performance Testing

[0089] The room temperature magnetic properties were tested according to GB / T 3217-2013 standard: Br=1.43 T, Hcj=1920 kA / m, (BH)max=402 kJ / m³. The amount of heavy rare earth Tb was 0.7 wt%, which meets the requirement of ≤0.8 wt%, as detailed in Table 1 below.

[0090] High-temperature magnetic properties were tested using the following method: remanence and coercivity were measured at temperatures of 20℃, 150℃, and 180℃, and the temperature coefficients were calculated as follows:

[0091] Remanence temperature coefficient α (20-150℃) = (Br 150 - Br 20 ) / [Br 20 [× (150-20)] × 100% = (1.285-1.43) / (1.43×130) × 100% = -0.113 % / ℃

[0092] Temperature coefficient of coercivity β(20-150℃) = (Hcj 150 - Hcj 20 ) / [Hcj 20 [× (150-20)] ×100% = (1123-1920) / (1920×130) × 100% = -0.53 % / ℃

[0093] The test method for high-temperature irreversible loss H_irr (150℃) is as follows: the magnet is kept in an open circuit at 150℃ for 2 hours, and after cooling to room temperature, the remanence loss rate is measured, and the result is 3.1%. The specific performance data at 150℃ and 180℃ are shown in Table 2 below.

[0094] This embodiment demonstrates that the composite addition of Cu, Ga, and Co to the basic alloy, combined with low-temperature Tb 70 Al 30The synergistic effect of grain boundary diffusion technology simultaneously achieves high room temperature magnetic properties (Br≥1.42T, Hcj≥1800kA / m) and excellent high temperature stability (β≥-0.55% / ℃, α≥-0.115% / ℃, H_irr≤3.5%) with extremely low heavy rare earth content (0.7 wt%).

[0095] II. Comparative Example 1 (C1)

[0096] Comparative Example 1 uses the same basic alloy composition as Example 1, namely containing 0.20% Cu, 0.10% Ga and 0.20% Co, but the diffusion process adopts the conventional high-temperature diffusion method of the prior art.

[0097] The specific process is as follows: TbH2 powder is used as the diffusion source. The TbH2 powder is mixed with anhydrous ethanol to form a slurry, which is then uniformly coated onto the magnet surface (coating thickness approximately 50 μm). After drying, the magnet is subjected to diffusion treatment at 920℃ for 3 hours in a vacuum heat treatment furnace, followed by secondary aging at 500℃ for 2 hours. The amount of heavy rare earth Tb is still controlled at 0.7 wt%.

[0098] Performance test results are: Br = 1.39 T, Hcj = 1950 kA / m, (BH)max = 380 kJ / m³. Tested at 150℃: Br 150 =1.235 T, Hcj 150 =1080 kA / m, α(20-150℃)=-0.124% / ℃, β(20-150℃)=-0.59% / ℃, H_irr(150℃)=4.5%.

[0099] Compared with Example 1, although C1 has a slightly higher room temperature coercivity (1950 vs 1920 kA / m), its remanence (1.39 vs 1.43 T), energy product (380 vs 402 kJ / m³), and all high-temperature stability indicators are inferior to E1. This indicates that the low-temperature diffusion process of the present invention (630-670℃ × 8-12h) can more effectively protect remanence and systematically improve high-temperature stability compared with conventional high-temperature diffusion (920℃ × 3h), under the same composition and heavy rare earth content.

[0100] III. Comparative Example 2 (C2)

[0101] The diffusion process of Comparative Example 2 was exactly the same as that of Example 1 (Tb 70 Al 30 Sputtering (650℃×10h), but without adding Cu, Ga, and Co composite elements to the base alloy (i.e., M=0), the base alloy composition is (Nd,Pr). 32 Fe_balB 1.0 .

[0102] Performance test results are: Br = 1.41 T, Hcj = 1680 kA / m, (BH)max = 390 kJ / m³. Tested at 150℃: Br 150 =1.250 T, Hcj 150 =905 kA / m, α(20-150℃)=-0.127% / ℃, β(20-150℃)=-0.62% / ℃, H_irr(150℃)=5.8%.

[0103] Compared with Example 1, it can be seen that without the composite addition of Cu, Ga, and Co, even with the exact same low-temperature diffusion process, the increase in coercivity is significantly reduced (1680 vs 1920 kA / m), and the irreversible loss at high temperatures increases substantially (5.8% vs 3.1%), with a marked deterioration in the temperature coefficient of coercivity. This indicates that the composite addition of Cu, Ga, and Co to the base alloy is indispensable for constructing ideal grain boundary diffusion channels, improving Tb diffusion efficiency, and enhancing temperature stability.

[0104] IV. Comparative Example 3 (C3)

[0105] Comparative Example 3 used a traditional heavy rare earth alloying method without grain boundary diffusion treatment. The basic alloy composition was the same as in Example 1 (containing 0.20% Cu, 0.10% Ga and 0.20% Co), but 2.0 wt% Tb (added in pure metal form) was added directly during the smelting and batching process.

[0106] The preparation process is as follows: proportioned batching → vacuum melting → hydrogen breaking + air jet milling (average particle size 3.5 μm) → magnetic field orientation molding → vacuum sintering at 1070℃ for 3 hours → first-stage aging at 900℃ for 1.5 hours → subsequent machining and surface protection. No grain boundary diffusion treatment is performed.

[0107] The performance test results are: Br = 1.34 T, Hcj = 1980 kA / m, (BH)max = 350 kJ / m³. Tested at 150℃: Br 150 =1.205 T, Hcj 150 =1120 kA / m, α(20-150℃)=-0.121% / ℃, β(20-150℃)=-0.58% / ℃, H_irr(150℃)=4.8%.

[0108] Compared with Example 1, it can be seen that the present invention achieves similar coercivity at 150°C (1123 vs 1120 kA / m) and 180°C (950 vs 940 kA / m) to 2.0 wt% Tb alloying (C3) through low-temperature grain boundary diffusion (E1) using 0.7 wt% Tb, but with significantly higher room-temperature remanence (1.43 vs 1.34 T), higher energy product (402 vs 350 kJ / m³), and lower high-temperature irreversible loss (3.1% vs 4.8%). This fully demonstrates that the present invention achieves efficient utilization of heavy rare earth elements, simultaneously obtaining excellent high-temperature stability and high room-temperature magnetic properties with extremely low heavy rare earth element content.

[0109] V. Comparative Analysis and Discussion of Example 1 and Comparative Examples

[0110] Table 1 compares the processes and room temperature magnetic properties of the above embodiments and comparative examples.

[0111] E1 0.20Cu + 0.10Ga + 0.20Co 0.7 <![CDATA[Tb 70 Al 30 Sputtering, 650℃×10h 1.43 1920 402 C1 0.20Cu + 0.10Ga + 0.20Co 0.7 <![CDATA[TbH₂ coating, 920°C × 3h]]> 1.39 1950 380 C2 0 (No additives) 0.7 <![CDATA[Tb 70 Al 30 Sputtering, 650℃×10h 1.41 1680 390 C3 0.20Cu + 0.10Ga + 0.20Co 2.0 (Alloyed) No diffusion 1.34 1980 350

[0112] Table 2 shows the high-temperature stability data of the above embodiments and comparative examples.

[0113] E1 1.285 1.235 1123 950 -0.113 -0.53 3.1 C1 1.235 1.180 1080 890 -0.124 -0.59 4.5 C2 1.250 1.190 905 740 -0.127 -0.62 5.8 C3 1.205 1.155 1120 940 -0.121 -0.58 4.8

[0114] Please see Figure 2 The above examples are compared with the comparative examples in terms of high-temperature stability. Based on the comparison data of E1 with C1, C2, and C3, the following conclusions can be drawn:

[0115] (1) Advantages of low-temperature diffusion process (E1 vs C1): Under the same basic alloy composition, the Tb used in this invention 70 Al 30 Compared to the conventional TbH2 coating + 920℃ × 3h high-temperature diffusion process, the sputtering + 650℃ × 10h low-temperature diffusion process, while exhibiting comparable room-temperature coercivity (1920 vs 1950 kA / m), results in an approximately 0.04 T increase in room-temperature remanence (1.43 vs 1.39 T), a 1.4 percentage point reduction in high-temperature irreversible loss (3.1% vs 4.5%), a 0.06% / ℃ decrease in the absolute value of the coercivity temperature coefficient (-0.53 vs -0.59 % / ℃), and a 0.011% / ℃ decrease in the absolute value of the remanence temperature coefficient (-0.113 vs -0.124% / ℃). This verifies the technical effectiveness of the 630-670℃ low-temperature diffusion temperature range and 8-12h time range described in claims 1 and 11. Low-temperature diffusion effectively suppresses the bulk diffusion of Tb into the grain interior, protecting remanence while improving coercivity, promoting the formation of a stable grain boundary phase structure, and improving high-temperature stability.

[0116] (2) Necessity of Cu, Ga, and Co composite addition (E1 vs C2): Without the addition of Cu, Ga, and Co, even with the same low-temperature diffusion process, the coercivity only reaches 1680 kA / m (not meeting the requirement of ≥1800 kA / m), and the high-temperature performance deteriorates across the board. This verifies the technical effect of the composite addition of 0.10-0.30% Cu, 0.05-0.15% Ga, and 0.10-0.30% Co to the basic alloy in claims 1 and 2. The synergistic effect of the three elements optimizes the grain boundary wettability and diffusion channels, enabling Tb to penetrate efficiently at low temperatures and form a uniform shell structure on the surface of the main phase.

[0117] (3) Advantages of efficient utilization of heavy rare earth elements (E1 vs C3): This invention achieves a high-temperature coercivity level similar to that of alloying with 2.0 wt% Tb with a diffusion content of 0.7 wt% Tb, while having a remanence 0.09 T higher, a magnetic energy product 52 kJ / m³ higher, and an irreversible loss 1.7 percentage points lower. This verifies the technical effect of using ≤0.8 wt% heavy rare earth elements in claim 12. Through the synergy of the base alloy and low-temperature diffusion, the reduction of heavy rare earth elements is achieved while systematically optimizing the stability of high-temperature magnetic properties.

[0118] (4) Achievement of overall performance indicators: E1 fully meets all the performance indicators defined in claims 13 and 14: Br≥1.42T (measured 1.43T), Hcj≥1800kA / m (measured 1920kA / m), β(20-150℃)≥-0.55% / ℃ (measured -0.53% / ℃), α(20-150℃)≥-0.115% / ℃ (measured -0.113% / ℃), H_irr(150℃)≤3.5% (measured 3.1%), and further achieves the preferred performance range of β≤-0.53% / ℃, α≤-0.113% / ℃, and H_irr≤3.1%.

[0119] The above are merely preferred embodiments of this application, and only specifically describe the technical principles of this application. These descriptions are only for explaining the principles of this application and should not be construed as limiting the scope of protection of this application in any way. Based on this explanation, any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application, as well as other specific embodiments of this application that can be conceived by those skilled in the art without creative effort, should be included within the scope of protection of this application.

Claims

1. A method for preparing a sintered NdFeB permanent magnet, characterized in that, Includes the following steps: (1) Prepare a base alloy, wherein the composition of the base alloy is (Nd, Pr) by weight percentage. a Fe bal B b M, where a ranges from 31 to 33 wt%, b ranges from 0.98 to 1.05 wt%, and M is a composite additive element containing 0.10 to 0.30 wt% Cu, 0.05 to 0.15 wt% Ga, and 0.10 to 0.30 wt% Co, with the balance being Fe; (2) The base alloy is prepared into powder, oriented by magnetic field and pressed into shape, and then vacuum sintered at 1060-1080℃, followed by first-stage aging treatment to obtain sintered magnet blank; (3) A Tb-Al based alloy thin film is deposited on the surface of the sintered magnet blank as a diffusion source, and then grain boundary diffusion heat treatment is carried out at 630-670°C under inert atmosphere protection. (4) Perform post-processing on the magnet after diffusion treatment.

2. The method according to claim 1, characterized in that, In step (1), the value of a ranges from 31.5 to 32.5 wt%, the content of Cu is 0.15 to 0.25 wt%, the content of Ga is 0.08 to 0.12 wt%, and the content of Co is 0.15 to 0.25 wt%.

3. The method according to claim 1, characterized in that, In step (2), the average particle size of the powder is 3.0 to 4.0 μm; the holding time of the vacuum sintering is 2 to 4 hours; the temperature of the first-stage aging treatment is 900 to 920℃ and the holding time is 1 to 2 hours; the density of the sintered magnet blank is ≥7.5 g / cm³.

4. The method according to claim 1, characterized in that, In step (3), the Tb-Al based alloy is Tb 70 Al 30 The thickness of the Tb-Al based alloy film is 10–30 μm.

5. The method according to claim 1, characterized in that, In step (3), the deposition method of the Tb-Al based alloy thin film is magnetron sputtering, vacuum evaporation, or ion plating; the conditions for magnetron sputtering are: vacuum degree better than 5.0 × 10⁻⁶. -4 The pressure is 0.5–1.0 Pa, and the sputtering power is 100–200 W; the grain boundary diffusion heat treatment time is 8–12 hours.

6. The method according to claim 1, characterized in that, In step (4), the post-processing of the diffused magnet includes: machining and surface protection treatment of the diffused magnet.

7. A sintered NdFeB permanent magnet, characterized in that, The permanent magnet is prepared by any one of claims 1 to 11, wherein the amount of heavy rare earth element Tb in the permanent magnet is ≤0.8 wt.

8. The sintered NdFeB permanent magnet according to claim 7, characterized in that, The permanent magnet meets the following performance indicators: Remanence at room temperature Br ≥ 1.42 T; Room temperature coercivity Hcj ≥ 1800 kA / m; The temperature coefficient of coercivity β in the range of 20-150℃ is ≥ -0.55% / ℃; The remanence temperature coefficient α in the range of 20-150℃ is ≥ -0.115 % / ℃; Irreversible loss of H at 150℃ irr ≤ 3.5%.

9. The sintered NdFeB permanent magnet according to claim 8, characterized in that, The permanent magnet satisfies the following conditions: a coercivity temperature coefficient β ≥ -0.53 % / ℃ in the range of 20-150℃, and / or a remanence temperature coefficient α ≥ -0.113 % / ℃ in the range of 20-150℃, and / or an irreversible loss H at 150℃. irr ≤ 3.1%.

10. The method according to any one of claims 1 to 6 or the permanent magnet according to any one of claims 7 to 9 in new energy vehicle drive motors, wind turbines or high-temperature industrial motors.